Anisotropic deformation mechanism of {110} hexagonal dislocation networks in BCC Iron. (15th January 2023) - Ghaffarian, Hadi; Jang, Dongchan
Abstract: Molecular dynamics simulation was performed to study the anisotropic mobility behavior of hexagonal dislocation networks (HDNs) in a series of bicrystalline pure Fe samples under a force-control in-plane shear deformation test. It is found that the mobility of HDN is mainly controlled by the characteristic features of <001> dislocations, which formed in the vicinity of ½<111> dislocations lying at the HDN. Furthermore, we elucidate the underlying mechanism of shearing in HDN as the variation of the length and the core energy of <001> dislocation lines with HDN misorientation angle. The energy barrier analysis of kink activities on the HDN plane is used to address the contribution of these geometrical and structural features to the in-plane shearing anisotropy of the HDN. Graphical abstract: Image, graphical abstract